2016
DOI: 10.1080/08927936.2015.1075299
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Lives of Companion Animals: Attachment and Subjective Claims by Owners of Cats and Dogs

Abstract: There is a growing body of scientific evidence supporting the existence of emotions in nonhuman animals. Companion-animal owners show a strong connection and attachment to their animals and readily assign emotions to them. In this paper we present information on how the attachment level of companion-animal owners correlates with their attribution of emotions to their companion cat or dog and their attribution of mirrored emotions. The results of an online questionnaire, completed by 1,023 Dutch-speaking cat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
87
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 53 publications
20
87
2
5
Order By: Relevance
“…Our results also demonstrate that respondents who owned a dog as their companion animal showed more concern for animal welfare. This result parallels a recent study by Martens et al (2016), which demonstrated a strong attachment between companion dogs and their owners, suggesting that pet (in particular dog) ownership is an important predictor of public attitudes toward animals.…”
Section: Religion and Pet Ownershipsupporting
confidence: 78%
See 4 more Smart Citations
“…Our results also demonstrate that respondents who owned a dog as their companion animal showed more concern for animal welfare. This result parallels a recent study by Martens et al (2016), which demonstrated a strong attachment between companion dogs and their owners, suggesting that pet (in particular dog) ownership is an important predictor of public attitudes toward animals.…”
Section: Religion and Pet Ownershipsupporting
confidence: 78%
“…We also confirmed that women show greater concern for animals than men (Bègue & Laine, 2017;Erlanger & Tsytsarev, 2012;Martens et al, 2016). This may be because women are socialized from birth in a caring and nurturing role, while men are brought up to be more utilitarian (Herzog, Betchart, & Pittman, 1991).…”
Section: Human Demographics and Their Interaction With Ethical Ideolosupporting
confidence: 69%
See 3 more Smart Citations